Decision Taken by an Emergency Meeting of Representatives of National Unions of Students in Vienna. 56/57 - General - No.608 14.XI.56-150 - Héderváry, Claire de (1956)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): World University Service Letter from World University Service detailing the text of a decision to establish a committee based in Vienna with the participation of Austrian National Union of Students, Coordinating Secretariat of National Union of Students, and World University Service. The committee will be responsible for assessing the needs of Hungarian students, providing information to relevant organizations, receiving and distributing material aid, and raising special funds.